Effect of Organic Matter Amendment on Lead Contamination in Roadside Soil and Plant - Sabaruddin, Sabaruddin; Budianta, Dedik; Mardia, Mardia (JOURNAL OF TROPICAL SOILS, 2010)
Lad Contamination in Roadside Soil and Plant and Effect of Organic Matter Amendment (Sabaruddin, D Budianta and Mardia):  Roadside soils and plants may be the most important sink of lead (Pb).  It has been widely known that soil organic matter (SOM) plays important roles in determining concentrations of metals in soil solution and their extractability from the soil.  To investigate Pb contamination in the roadside soils and plants, as well as the effect of organic matter (OM) on the soluble Pb in the roadside soils, surface soils (0 to 20 cm) were collected from a busy road.   The soils were incubated for 4 weeks under room temperature after being treated with 0, 30, 60 and 90 Mg ha-1 of OM.  Leaves of oil palms (Elaeis guineensis) planted on the roadside were also analyzed for Pb content.  Current study revealed that Pb content in roadside soils and leaves of oil palm was 1.5 and 5.5 times higher than the safe level of Pb in soil and plant.  It confirms that both soil and plant at the study site were contaminated by Pb.  Current study also showed that SOM amendment significantly (P<0.01) affected soluble Pb content in the soils.  Adding OM to the soil at 30 Mg ha-1 to correct the level of SOC from very low to low was sufficient to significantly reduce soluble Pb in the soils.  However, the application of 60 Mg ha-1 of OM triggered the increases in soluble Pb in the soils.  Further increases in OM application to 90 Mg ha-1 resulted in significant increases in soluble Pb as compared with that in the soil receiving 30 Mg ha-1 of OM.  In spite of the increases, the level of soluble Pb in the soils receiving 60 and 90 Mg ha-1 of OM was still much below the safe level of Pb in soil.